2006
DOI: 10.1093/deafed/enl009
|View full text |Cite
|
Sign up to set email alerts
|

Focus-on-Form Instructional Methods Promote Deaf College Students' Improvement in English Grammar

Abstract: Focus-on-form English teaching methods are designed to facilitate second-language learners' noticing of target language input, where "noticing" is an acquisitional prerequisite for the comprehension, processing, and eventual integration of new grammatical knowledge. While primarily designed for teaching hearing second-language learners, many focus-on-form methods lend themselves to visual presentation. This article reports the results of classroom research on the visually based implementation of focus-on-form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…Berent et al [133] implemented a visually based focus-on-form approach to writing instruction in which learners were made aware of the grammatical form of language features that they were already able to use communicatively. Experimental groups in this study demonstrated significantly greater improvement in English grammatical knowledge relative to the control group after a 10-week remedial grammar course.…”
Section: Research On Writing Development Of the D/dhhmentioning
confidence: 99%
“…Berent et al [133] implemented a visually based focus-on-form approach to writing instruction in which learners were made aware of the grammatical form of language features that they were already able to use communicatively. Experimental groups in this study demonstrated significantly greater improvement in English grammatical knowledge relative to the control group after a 10-week remedial grammar course.…”
Section: Research On Writing Development Of the D/dhhmentioning
confidence: 99%
“…The development of spoken English language and literacy skills is a challenging task for hearing‐impaired learners because of hearing loss restricting the intake of linguistic information through the auditory channel (Berent, Kelly and Aldersley et al., 2007; Bochner and Albertini, 1988). The acquisition of morphology, syntax and vocabulary such as inflectional affixes, function words and deviations from canonical word order are particular areas of difficulty (Bochner and Bochner, 2009).…”
Section: Related Workmentioning
confidence: 99%
“…Since deaf learners rely heavily on visual and printed input in their language acquisition, Bochner and Bochner (2009) advocate the use of communication methods that foster meaningful face‐to‐face social interactions, such as speech reading, finger spelling and cued speech, to facilitate the visual processing of linguistic information. The results of the study of Berent et al. (2007) showed that visual input enhancement proved to be an effective pedagogical tool for hearing‐impaired college students.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, they will likely be able to determine, and even set up a benchmark for, 'the extent to which learner attention should be directed' (Doughty 2004: 187). Current research has provided evidence showing that compound enhancement is not always necessary (see Williams and Evans 1998;Berent et al 2007).…”
Section: Te and Overusementioning
confidence: 99%